The incidence and determinants of the meconium-aspiration syndrome among mothers with meconium-stained amniotic fluid after emergency cesarean section: A prospective cross-sectional study in a specialized hospital, south Ethiopia - Tantu, Temesgen; Zewdu, Dereje; Degemu, Fikretsion; Yehualeshet, Tsiyon (Frontiers in Pediatrics, 2023)
Background: Meconium aspiration syndrome is respiratory distress diagnosed in neonates delivered with meconium-stained amniotic fluid which is unexplained by other pathologies. It has severe neonatal respiratory complications and a significant impact on the prevalence of neonatal mortality. Objective: To identify the incidence and determinants associated with meconium aspiration syndrome among mothers with meconium-stained amniotic fluid after emergency cesarean section in wolkite university specialized hospitals in Ethiopia from September 1, 2021, to August 30, 2022 Method: Institution-based cross-sectional study was done prospectively through meticulous chart review and interviews with 275 mothers with meconium-stained amniotic fluid who gave birth with emergency cesarean section. Data were entered using Epi data 7 and analyzed with SPSS 26. The association between independent variables and the meconium-aspiration syndrome was estimated using an odds ratio with 95% confidence intervals. The statistical significance of the association was declared at P-value < 0.05 Result: The prevalence of the meconium-aspiration syndrome is 28.7%. the factors associated are: latent phase (AOR 2.580; 95% CI: 1.126,5.913), low 1st minute APGAR score (AOR 2.43;95% CI: 0.892,6.625) and thick meconium (AOR 31.018; 955 CI: 9.982,96.390). The neonatal death associated with meconium aspiration syndrome is 1.8%, and thick meconium contributed to 65% of admission to the neonatal intensive care unit and all deaths. Conclusion: The prevalence of meconium aspiration syndrome is high for which thick meconium, meconium at early labor, and low APGAR scores contributed much. Thich meconium has a substantial effect on neonatal mortality and morbidity. Therefore, an improvement in the quality of obstetric and neonatal care through early intervention in the case of thick meconium and meconium in the early phase of labor is recommended.